Fast implementations of block motion estimation algorithms in video encoders - Koduri, Naga Rohini (Department of Electrical Engineering, 2015)
This research is aimed at designing and implementing novel fast algorithms for speeding up the encoding process. The objective of this study was to come up with algorithms which can estimate the data significantly faster than the existing algorithms, whilst ensuring acceptable video quality.